2012
DOI: 10.1074/jbc.m112.367581
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Pokeweed Antiviral Protein (PAP) by Turnip Mosaic Virus Genome-linked Protein (VPg)

Abstract: Pokeweed antiviral protein (PAP) from Phytolacca americana is a ribosome inactivating protein (RIP) and an RNA N‐glycosidase that removes specific purine residues from the sarcin/ricin (S/R) loop of large rRNA, arresting protein synthesis at the translocation step. PAP is also a cap‐binding protein, and is a potent antiviral agent against many plant, animal, and human viruses. To elucidate the mechanism of RNA depurination, and to understand how PAP recognizes and targets various RNAs, the interactions between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 52 publications
(44 reference statements)
0
34
0
Order By: Relevance
“…This viral peptide serves as an analog of the 5ʹ-m 7 G cap of viral RNA, and has been shown to play an important role in mRNA translation since it interacts with the cap-binding proteins (e.g., eIF4E, eIFiso4E, eIF4F, eIFiso4F) [64,65]. Our laboratory has shown that PAP interacts with VPg (K d is 29.5 ± 1.8 nM) and inhibits PAP's activity in a dose-dependent manner [57], perhaps providing an evolutionary advantage for the virus to…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This viral peptide serves as an analog of the 5ʹ-m 7 G cap of viral RNA, and has been shown to play an important role in mRNA translation since it interacts with the cap-binding proteins (e.g., eIF4E, eIFiso4E, eIF4F, eIFiso4F) [64,65]. Our laboratory has shown that PAP interacts with VPg (K d is 29.5 ± 1.8 nM) and inhibits PAP's activity in a dose-dependent manner [57], perhaps providing an evolutionary advantage for the virus to…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, PAP isoforms selectivity for different ribosomes and RNAs varies (e.g., PAP-I, found in spring leaves of the pokeweed plant, exhibits RC 50 of 1.5 nM towards rat liver ribosomes and 4.7 nM towards E. coli ribosomes [38]; PAP-S1, an isoform found in seeds of the plant, exhibits IC 50 of 3.2 nM towards rat liver ribosomes and 280 nM towards E. coli ribosomes [41,42]; whereas α-PAP, expressed in all organs of the plant, exhibits IC 50 of 1.3 nM towards rat liver ribosomes and 25 nM towards E. coli ribosomes [13,42]. In recent years, a viral protein (VPg), linked to genome of turnip mosaic virus (TuMV) was shown to inhibit PAP activity in vitro [13,57]. This viral peptide serves as an analog of the 5ʹ-m 7 G cap of viral RNA, and has been shown to play an important role in mRNA translation since it interacts with the cap-binding proteins (e.g., eIF4E, eIFiso4E, eIF4F, eIFiso4F) [64,65].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…the genus Potyvirus, whose members are characterized by having a VPg protein at the 5' end of their genome. Recently it was shown that the VPg of a potyvirus binds PAP with high affinity, being a potent inhibitor of PAP depurination (Domashevskiy et al, 2012), which can explain the lack of antiviral effects observed at the local level. However, pretreatment with PAP before inoculation could prepare the plant to avoid viral infection as observed in our experiments where the virus was inoculated 4 days after PAP treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies examined the interactions between PAP (cap-binding protein) and VPg from TuMV [70], and revealed that VPg competes with TEV RNA for PAP binding [71]. These PAP-VPg interactions are enthalpically-driven and entropically favorable [70], exhibiting a similarity to those of eIFiso4E-and eIFiso4F-VPg binding [63].…”
Section: Interactions Between Pokeweed Antiviral Protein and Potyviramentioning
confidence: 99%